Validation of the Parental Self‐Efficacy in Managing Child Food‐Induced Anaphylaxis (PSEMA) Questionnaire for Ethnic Chinese Families With Food‐Allergic Children - Christy Wing Man Leung; Nam Sze Cheng; Daphne Hoh Ching Ng; Yin Shan Wong; Michał Ordak; Ting Fan Leung (Clinical & Experimental Allergy, 2026)
Summary The Traditional Chinese version of PSEMA questionnaire (PSEMA‐TC) is a valid and reliable tool. Allergy education may enhance parental confidence and self‐efficacy in anaphylaxis management.